Guided imagery terhadap tingkat fatigue pada pasien dengan gagal ginjal kronik yang menjalani hemodialisis - Andoko Andoko; Ermawati Ermawati (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2020)
The effects of guided imagery on fatigue in patients with chronic kidney disease undergoing hemodialysisBackground: Kidney and urinary tract diseases contribute 850,000 mortality rates placing them as the disease burden in the world. One of the general nursing problems suffered from chronic kidney disease patients who undergo hemodialysis is fatigue. The intervention that can be given to overcome the fatigue on the clients is a relaxation therapy strategy. A well-recommended therapy to relieve the fatigue is known as guided imagery.Purpose: Knowing the effect of guided imagery on fatigue in patients with chronic kidney disease undergoing hemodialysis.Methods: A quantitative with a quasi experiment technique and nonequivalent control group design. The population of this study included 67 patients registered with chronic kidney disease undergoing hemodialysis at the hospital. The purposive sampling technique took 32 people. The samples were distributed into two groups; 16 people in each group. The analysis was a thorough T-Test.Result: Finding that the mean of the fatigue levels of experiment and control groups were different. The mean score before the intervention was 0.352, while the score after the intervention was 2.000 (p-value 0.025).Conclusion: There was the effect of guided imagery on fatigue in patients with chronic kidney disease undergoing hemodialysis. Chronic kidney disease patients who undergo hemodialysis should independently and regularly do relaxation therapy because this therapy is easy to apply and proven effective to reduce fatigue.Keywords: Guided Imagery; Fatigue; Chronic Kidney Disease; HemodialysisPendahuluan: Penyakit ginjal dan saluran perkemihan berkontribusi menjadi beban penyakit di dunia dengan sekitar 850.000 kematian setiap tahun. Masalah keperawatan yang banyak dihadapi pasien gagal ginjal kronik yang menjalani hemodialisa umumnya adalah fatigue (kelemahan). Intervensi keperawatan untuk membantu klien dalam mengatasi masalah kelemahan diantaranya melalui strategi pemberian terapi relaksasi. Salah terapi relaksasi yang dipercaya dapat membantu mengatasi fatigue adalah guided imagery.Tujuan: Diketahuinya pengaruh guided imagery terhadap tingkat fatigue pasien gagal ginjal kronik yang menjalani hemodialisis.Metode: Penelitian kuantitatif, desain quasi eksperiment dengan rancangan nonequivalent control group design. Populasi pasien gagal ginjal kronik yang menjalani hemodialisa yang berjumlah 67 orang, besar sampel yang diambil sebanyak 32 orang yang terbagi dalam 2 kelompok, masing-masing kelompok sebanyak 16 orang, teknik pengambilan sampel menggunakan purposive sampling. Analisis menggunakan uji t-test.Hasil: Didapatkan selisih rata-rata tingkat fatigue antara kelompok intervensi dengan kelompok kontrol sebelum perlakuan adalah 0,352 dan setelah perlakuan 2,000 (p-value 0,025).Simpulan: Ada pengaruh guided imagery terhadap tingkat fatigue pasien gagal ginjal kronik yang menjalani hemodialisis. Bagi pasien gagal ginjal kronik yang menjalani hemodialisa hendaknya dapat mempergunakan terapi relaksasi secara mandiri dan teratur karena selain mudah dilakukan, terapi ini telah terbukti efektif dalam menurunkan tingkat kelelahan.